CLT-Groups with Hall S-Quasinormally Embedded Subgroups - Li, Shirong; Liu, Jianjun (Ukrains’kyi Matematychnyi Zhurnal, 2014)
A subgroup H of a finite group G is said to be Hall S-quasinormally embedded in G if H is a Hall subgroup of the S-quasinormal closure H SQG . We study finite groups G containing a Hall S-quasinormally embedded subgroup of index p n for each prime power divisor p n of the order of G.